Therapeutic drug monitoring of fenfluramine in clinical practice: Pharmacokinetic variability and impact of concomitant antiseizure medications. Issue 3 (15th January 2022) - Schoonjans, An‐Sofie; Roosens, Laurence; Dewals, Wendy; Paelinck, Bernard P.; Ceulemans, Berten
Abstract: Objective: This study was undertaken to determine the plasma concentration and pharmacokinetic variability of fenfluramine (FFA) and its main active metabolite norfenfluramine (norFFA) in relation to the prevalence of adverse effects in patients with refractory epilepsy treated with FFA. In addition, the interaction with concomitant antiseizure medications including stiripentol (STP) is studied. Methods: Patients were recruited at our center from two open‐label sources, an investigator‐initiated observational study and an international multicenter extension study. Venous blood samples were collected between June 2015 and December 2020. Plasma FFA and norFFA concentrations were determined by liquid chromatography tandem spectrometric analysis. Clinical data were collected retrospectively. Intrapatient coefficient of variation was calculated for all patients with at least three samples. Interpatient variability was calculated based on the concentration to weight‐adjusted dose ratio (C/D) of all patients. Results: We collected 321 samples from 61 patients (49 with Dravet syndrome, seven with Lennox–Gastaut syndrome, and five with a developmental and epileptic encephalopathy). With a mean daily dose of .33 mg/kg/day (SD = ±.16), the median FFA plasma concentration was 41.4 µg/L (range = 5.1–712.5) and median norFFA concentration 28.1 µg/L (range = 2.6–149.6). The FFA plasma concentration was linearly related to the daily dose ( p  < .001) and norFFA levels ( p  < .001). The C/D of FFA increased with age ( p  < .001). Median FFA C/D was 428% higher ( p  < .001), norFFA C/D 83% lower ( p  < .001), and norFFA/FFA 23% lower ( p  < .001) in patients treated with STP comedication. Higher FFA concentration was associated with fatigue ( p  = .001) and somnolence ( p  < .001), but not anorexia ( p  = .0619) or reduction in seizure frequency ( p  = .772). Gender and other ASMs were not associated with significant variations in (nor)FFA C/D ratio. Significance: Most FFA levels are in the lower range (<50 µg/L), although a high interpatient and intrapatient variability is present. In combination with STP, the dose of FFA should be reduced.